Men of steel, women of wonder : modern American superheroes in contemporary art - Bentti, Alejo (The University of Arkansas Press, 2019)
Intro; Contents; Zero Issue -- Issue 00; Foreword / Rod Bigelow; Acknowledgements; Of Waistbands and Journeys: An Introduction; Works in Exhibition; Image Credits; The Hero We Know -- Issue 01; The Spectacular Banality of the Superhero / Bart Beaty; Origin Stories -- Issue 02; Manly Workers and Pin-up Girls: Sources for Comic Book Superheroes in 1930s American Visual Culture / Erika Doss; Glimpsing Humanity -- Issue 03; When They Bleed: Our Vulnerable American Gods / Alejo Benedetti; Defender of Innocents -- Issue 04; Superheroes: Dreaming Utopia in Art / Andrianna Campbell; Index